Production Efficiency Strategy Strategy in Orca Powergear: A Kepner Tregoe Decision Making Analysis - Bungaran, Muhammad Faris Ghiyats; Hasyimi, Valid (Dinasti Publisher, 2026)
Orca Powergear, a motorcycle apparel manufacturer in Bandung, Indonesia, faces a persistent production efficiency problem where customer orders across four product lines consistently exceed available monthly production capacity. This study investigates the root cause and identifies the most appropriate strategy to resolve it. Three analytical frameworks are applied sequentially. Herzberg's Two-Factor Theory, administered through a 14-question Likert scale questionnaire to all 27 sewing team members, validates the presence of a workforce motivation problem. The Kepner-Tregoe Framework traces the root cause through a Focus Group Discussion and the Five-Whys technique. The Analytic Hierarchy Process evaluates three strategic alternatives against four decision criteria using pairwise comparison judgments from four subject matter experts. Results reveal active dissatisfaction with the fixed monthly salary system, with salary fairness and payroll policy clarity scoring means of 1.74 and 2.11 in the Disagree range. The root cause is identified as the absence of a human resource system linking worker effort to financial reward. The Analytic Hierarchy Process identifies the pay-per-item-sewed payroll system as the leading strategy with a Normals score of 70.46%. The study concludes that this payroll transition is the most appropriate and feasible strategy for closing the production efficiency gap at Orca Powergear.